Simplify 4*√12 + 3*√48?

0 votes
asked Dec 23, 2012 in Mathematics by anonymous
    

1 Answer

0 votes

4*√12 + 3*√48

simplifying the radicals, we get:


= 4*(√4)*(√3) + 3*(√4)*(√12)
 

the second of which can be further broken down

= 8*√3 + 6*√12


= 8*√3 + 6*(√4)*(√3) 


= 8*√3 + 12*√3


= (√3)*[8 + 12]

therefore you get:


= 20*√3

answered Dec 23, 2012 by anonymous

Related questions

+2 votes
1 answer 354 views
354 views asked Dec 23, 2012 in Mathematics by FLoops ~Expert~ (2,117 points)
0 votes
1 answer 40 views
+2 votes
0 answers 408 views
408 views asked Dec 23, 2012 in Mathematics by JPx ~Expert~ (379 points)
0 votes
0 answers 55 views
0 votes
0 answers 69 views
69 views asked Dec 23, 2012 in Mathematics by anonymous



...